2006
DOI: 10.1038/sj.ijo.0803487
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein, metabolism, and body-weight regulation: dose–response effects

Abstract: Body-weight management requires a multifactorial approach. Recent findings suggest that an elevated protein intake seems to play a key role herein, through (i) increased satiety related to increased diet-induced thermogenesis; (ii) its effect on thermogenesis; (iii) body composition; and (iv) decreased energy-efficiency, all of which are related to protein metabolism. Supported by these mechanisms, relatively larger weight loss and subsequent stronger body-weight maintenance have been observed. Increased insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
108
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 63 publications
(83 reference statements)
4
108
0
4
Order By: Relevance
“…18 Finally, additional protein intake limited weight regain after weight loss in overweight subjects, which was accompanied by a slower increase in respiratory quotient an improved body composition and fat distribution. 19 The above data may suggest that the interaction between protein intake, insulin and glycemic responses and substrate partitioning may be one of the putative mechanisms involved in body weight regulation and insulin sensitivity, besides the other mechanisms suggested by WesterterpPlantenga et al 1 Although the relationship may be mechanistically plausible, there is great lack of (long-term) studies, taking all relevant factors into account. Furthermore, it is obvious that insulinemic and glycemic responses also depend on the glycemic index of the diet, whether protein replaces carbohydrates or fats in the diet and the type of dietary protein.…”
Section: Protein Insulin Secretion and Substrate Partitioningmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Finally, additional protein intake limited weight regain after weight loss in overweight subjects, which was accompanied by a slower increase in respiratory quotient an improved body composition and fat distribution. 19 The above data may suggest that the interaction between protein intake, insulin and glycemic responses and substrate partitioning may be one of the putative mechanisms involved in body weight regulation and insulin sensitivity, besides the other mechanisms suggested by WesterterpPlantenga et al 1 Although the relationship may be mechanistically plausible, there is great lack of (long-term) studies, taking all relevant factors into account. Furthermore, it is obvious that insulinemic and glycemic responses also depend on the glycemic index of the diet, whether protein replaces carbohydrates or fats in the diet and the type of dietary protein.…”
Section: Protein Insulin Secretion and Substrate Partitioningmentioning
confidence: 99%
“…In their literature review, Westerterp-Plantenga et al 1 describe processes involved in the relation between dietary protein and body weight management. There is consistent evidence that a relative increase in protein content of the diet may increase satiety and reduce energy intake during ad libitum feeding conditions (as reviewed in WesterterpPlantenga 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary protein, depending on its source, contributes strongly to short-term satiety and suppresses FI more than carbohydrate as indicated by quantitative and subjective measures 8 in both obese (OB) and normal weight (NW) adults. 9 Furthermore, while the relationship between food ingestion and short-term satiety and FI is affected by obesity and hyperinsulinemia in adults, 10 there are no reports of the effect of obesity in children on the regulation of short-term FI. However, adiposity may be a factor because lower compensation to fixed size carbohydrate preloads in 3-to 5-year-old girls was associated with increased body fatness.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that weight loss (8.9 v. 5.1 kg) and fat loss (7.6 v. 4.3 kg) were higher in the high-protein group, partly due to a lower energy intake (5.0 MJ/d v. 6.2 MJ/d, P, 0.05) (Skov et al 1999). Here, 25 % energy from protein at an energy intake of 5 MJ/d implies 75 g/d protein; in absolute terms a normal protein intake with neutral energy balance as a reference (Westerterp-Plantenga et al 2006). Therefore, in absolute terms, in fact, a normal protein intake was compared with a low-protein intake.…”
mentioning
confidence: 99%
“…Similarly, recommendations of 'high-protein weight-maintenance diets' only suggest keeping protein intake as g/d at the same level, i.e. representing 10-15 % energy with neutral energy balance, as a reference (Westerterp-Plantenga et al 2006). For example, moderately obese men and women who consumed 18 % energy intake as protein regained less weight, i.e.…”
mentioning
confidence: 99%